New hart's rules: The handbook of style for writers and editors - Ritter, R. M. (New York Oxford university press, 2005)
Hart's Rules for Compositors and Readers at the University Press, Oxford was first printed in 1893. This classic reference work for writers, editors, and publishers was in print through 39 editions for nearly one hundred years. New Hart's Rules is a brand-new text that brings the principles of the old text into the 21st century, providing answers to questions of editorial style for a new generation of professionals. Writers and editors of all kinds will find this handy guide an indispensable companion in their work. Twenty chapters give information on all aspects of writing and of preparing copy for publication, whether in print or electronically. New Hart's Rules covers a broad range of topics including publishing terms, layout and headings, how to treat illustrations, hyphenation, punctuation, UK and US usage, bibliographies and notes, and indexing. The chapters have been compiled by a team of experts and consultants, and the book draws on the unrivalled expertise of Oxford's Reference Department. It is also endorsed by the Society for Editors and Proofreaders. The text is designed and organized for maximum accessibility with clearly displayed examples throughout. Authoritative and comprehensive, New Hart's Rules is the essential desk guide for all writers and editors, and together with the New Oxford Spelling Dictionary and the New Oxford Dictionary for Writers and Editors forms the complete editorial reference set.